2015
DOI: 10.5430/crim.v2n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasmapheresis in adult respiratory distressed syndrome due to meningococcemia with disseminated intravascular coagulation - a case report

Abstract: Background: The aim of the present case report is to assess the efficiency of plasmapheresis in patients detected with meningococcemia since this procedure seems to lower circulating levels of endotoxin while it may also eliminate activated complement, clotting factors and lysosomal enzymes resulting from thromboplastin and activated granulocytes. Objective: Pay attention to plasmapheresis in Adult Respiratory Distressed Syndrome (ARDS) due to meningococcemia with disseminated intravascular coagulation (DIC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that plasmapheresis could be a useful adjunct to mechanical ventilation in acute respiratory failure. 36 , 37 In addition, clinical studies show that blood purification techniques, play a key role in effectively reducing the mortality of patients with severe COVID-19. 7 However, the evidence to date is insufficient to recommend the routine use of plasmapheresis to correct the hypoxemia, which can lead to multiorgan dysfunction due to advanced modes of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that plasmapheresis could be a useful adjunct to mechanical ventilation in acute respiratory failure. 36 , 37 In addition, clinical studies show that blood purification techniques, play a key role in effectively reducing the mortality of patients with severe COVID-19. 7 However, the evidence to date is insufficient to recommend the routine use of plasmapheresis to correct the hypoxemia, which can lead to multiorgan dysfunction due to advanced modes of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of a patient with meningococcemia with DIC, TPE can eliminate the activation of complement, coagulation factors, and lysosomal enzymes rather than reduce the concentration of endotoxin in the patient’s blood, thereby restoring the normal coagulation mechanism and correcting the abnormality of DIC and coagulation index. 12 However, the protective mechanism of TPE in sepsis-associated DIC patients is still unclear, and it is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%